A história não é bem essa: o monumento comemorativo como elemento dos conflitos sociais latino americanos - Masafret, Ivan Luis Palmeira Camardelli (2011)
After finding empirical use of specific public art monuments, as a prominent element in many social conflicts, to draw the main objective of this thesis, understand why certain memorials of public art as symbolic elements are constituted in loco conflicts linked by particular characteristics . Investigated the relevance of this phenomenon in the twentyfirst century - which ostensibly was exemplified in this work - attention has focused on cases of Latin American continent in the first decade of this century has had major political changes. The survey covered countries like Brazil, Venezuela, Cuba and Argentina. These countries were found exmplos different at the same time, obeyed certain pattern in the use dstes symbols. Social conflict in Argentina, involving the monument to General and former president Julio Argentino Roca, the case has been shown more useful for the sociological analysis of the phenomenon, since the course of events were contemporaneous research on the spot. Given the problem, research efforts focused on understanding the circumstances in which certain public art memorials are to be constituted as tools of social movements to demand, in order to give visibility to their protests. The methodology included interviews with key actors involved in conflicts as well as a literature search which comprised elements from historical monuments to figures portrayed in news media published in formal and informal, which in turn were responsible for connection establishment data, languages, accents, stories and social actions engaged, moreover a vast amount of material was researched imagery. Reply to conflicts envision the use of the monument would be co-opted as a symbolic element of the strategies involved in the conflict and understand what the real significance of the monuments in these conflicts are issues that the research attempts to remedy.